2022
DOI: 10.3390/membranes12070699
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Based Cathode Catalysts for Oxygen-Reduction Reaction in an Anion Exchange Membrane Fuel Cell

Abstract: A novel cobalt-chelating polyimine (Co-PIM) containing an additional amine group is prepared from the condensation polymerization of diethylene triamine (DETA) and terephthalalehyde (PTAl) by the Schiff reaction. A Co, N-co-doped carbon material (Co-N-C), obtained from two-stage calcination in different gas atmospheres is used as the cathode catalyst of an anion exchange membrane fuel cell (AEMFC). The Co-N-C catalyst demonstrates a CoNx-type single-atom structure seen under high-resolution transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…We demonstrated in Equation (1) that one O 2 molecule and one water molecule can be fully reduced to four hydroxyl ions (OH − ) by cathode catalysts in an alkaline solution, following the 4e-pathway. However, HO 2 − is an unavoidable intermediate by-product [ 30 , 31 , 32 , 33 , 40 ] due to the incomplete ORR (oxygen reduction reaction) in an alkaline medium (Equation (2)). Based on Equation (2), the reduction reaction can continue further after the supply of two additional electrons, the so-called 2e-pathway (Equation (2) plus Equation (3)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated in Equation (1) that one O 2 molecule and one water molecule can be fully reduced to four hydroxyl ions (OH − ) by cathode catalysts in an alkaline solution, following the 4e-pathway. However, HO 2 − is an unavoidable intermediate by-product [ 30 , 31 , 32 , 33 , 40 ] due to the incomplete ORR (oxygen reduction reaction) in an alkaline medium (Equation (2)). Based on Equation (2), the reduction reaction can continue further after the supply of two additional electrons, the so-called 2e-pathway (Equation (2) plus Equation (3)).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the trouble of preparing the macrocyclic structure and the addition of a carbon matrix such as carbon black (CB), we have prepared many nitrogen-containing polymers (N polymers). The N polymers can chelate with cobalt ions (Co(II)) and calcine to create a Co–N–C structure [ 30 , 31 , 32 , 33 ] without the addition of any CB.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolyzer prepared by Wu et al only needs 1.644 V to reach a large current of 1A (Wu et al, 2022). Cheng et al and Hsieh et al prepared Co-N-C catalyst and reached max power density of 275 and 361 mW cm −2 in AEMFCS (Cheng et al, 2022;Hsieh et al, 2022).…”
Section: Transition Metal Nitride For Her/hor In Alkaline Solutionmentioning
confidence: 99%
“…Among the studied nonnoble metal catalysts, transition metals and nitrogen-doped carbon (M-N-C, M: Fe, Co, Mn, Ni, etc.) catalysts have received great attention because of their good catalytic activity, ideal stability, and cost-effective scalable synthesis [9][10][11][12][13][14][15][16][17][18][19][20]. Previous researches have reported that the electrocatalytic performance of the M-N-C catalysts follows the order of Fe > Co > Mn > Ni in alkaline electrolytes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%